On the possibility of replacement of calcium carbonate by a high-performance, economically viable filler in polyethylene composites. (February 2023) - Hesabi, Mohammadnabi; Brennan, Shane; Boulard, Quentin; Le Blanc, Francois; Major, Ian
Calcium carbonate (CaCO3 ) is frequently added to polyethylene (PE) as a filler to reduce costs. An alternative to CaCO3, calcium fluoride (CaF2 ) was proposed in this research. PE/CaCO3 and PE/CaF2 composites in a wide composition range (0–60 wt.%) were prepared through a parallel twin screw extruder. Results indicated better interaction of CaF2 with PE matrix which improved samples yield stress. Statistical analysis showed the filler type was more influential factor on the yield stress while filler loading was not a statistically significant one. In contrast, crystallinity was strongly depended on the filler loading. The dynamic mechanical and rheological investigations revealed that PE/CaF2 composites had higher stiffness at ambient temperature and possessed lower viscosity below 40 wt.% of filler loading compared to PE/CaCO3 which could reduce the processing cost. Therefore, regarding its low price and good functional properties, CaF2 can be a promising alternative to CaCO3 .